The Impact of COVID-19 Pandemic on Unemployment Levels in Kurdistan Region - Hamin K. Dizyee; Bayar Gardi; Pshdar Abdalla Hamza; Rizhin Nuree Othman; Khowanas Saeed Qader; Sanarya Adnan Anwer; Hawkar Anwar Hamad (QALAAI ZANIST JOURNAL, 2023)
The purpose of this study is to see how the spread of the covid-19 pandemic impacts unemployment rates, in order to aid authorities in containing the crisis and reducing the negative effects of the pandemic on the economy's variables, particularly employment levels. As a result, the crisis resulting from the Covid-19 pandemic is a multifaceted crisis that necessitates responses to monetary, financial, and health policies. The crisis also highlighted the need to prioritize spending on the health sector while providing health protection for employment in various sectors to support its ability to resist diseases in a way that ensures that they continue to work and do not reduce their productivity in times of heaviness, in addition to continue to promote informal employment, which was severely harmed as a result of the spread of covid-19